Making Polar and Ocean Governance Future-Proof - Hansen-Magnusson, Hannes (Politics and Governance, 2022)
Governance institutions of the polar regions, as well as global oceans, may hold room for improvement in terms of effectiveness but, on the whole, their existence can be regarded as a success story. The arrangements managed to pool responsibility for regional resources amid Cold War geopolitics, mostly by delegating discussions to science committees. Changing global climate, however, provides considerable challenges to these governance arrangements. It begs the question of how the success story can be continued into the future. After sketching the emergence of polar and ocean governance and their core organizational principles during the 20th century, this article identifies some of the challenges linked to global warming that have been altering the context of governance fundamentally. The article discusses emerging issues that warrant attention, but which may be difficult to accommodate in present governance networks. Ultimately, the article argues that anchoring principles of “responsibility” that take into account the relational quality of polar and ocean spaces is key to any institutional design that seeks to take governance arrangements into the 21st century and beyond.